Ongkara Pranava Sebuah Konsep Ritual Dalam Diri - Ni Made Evi Kurnia Dewi (Kamaya: Jurnal Ilmu Agama, 2021)
This paper contains about Ongkara Pranava, the concept of ritual within the self. Ongkara Pranava is a sacred mantra that many Hindus chant in the archipelago, and even in the world. Another name for Ongkara is Pranava, which means "born of prana". Prana is another name for breath, more precisely, breath is the grossest aspect of prana, every breath that enters and leaves through human breathing is Ongkara. The human body is Ongkara. Breathing is an activity to cultivate the noble qualities within, to grow the Supreme consciousness and to become Consciousness itself. Accustomed to managing and practicing mindfulness through Ongkara meditation, the mantra itself can act as a map and at the same time a vehicle to run the boat of human self-awareness from the swift and complex currents of human thought, crossing the tidal waves originating from the currents of our own thoughts to improve quality. self and lead human consciousness to the Supreme consciousness. Ongkara Pranava, the concept of ritual within is studied using a qualitative descriptive method, the data collection technique used is a document study or literature study, then the data that has been collected will be analyzed descriptively qualitatively to obtain related conclusions about Ongkara Pranava, the concept of ritual within. Keywords: Ongkara Pranava, Mantra